Genomic imbalances detected through array CGH in fetuses with holoprosencephaly - Isabela Nelly Machado; Juliana Karina Heinrich; Ricardo Barini (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Holoprosencephaly (HPE) is heterogeneous in pathogenesis, integrating genetic susceptibility with the influence of environmental factors. Submicroscopic aberrations may contribute to the etiology of HPE. Our aim was to report the molecular analysis of 4 fetuses with HPE and normal metaphase karyotype. METHOD: A whole genome BAC-array based Comparative Genomic Hybridization (array CGH) was carried out in fetal blood samples. All potential cytogenetic alterations detected on the arrays were matched against the known copy number variations databases. RESULTS: The array CGH analysis showed copy number gains and losses in all cases. We found a recurrent deletion in 15q14 (clone RP11-23J11) and in 15q22 (clone RP11-537k8) in 2 out 4 cases analyzed. We also observed submicroscopic gain in 6p21 in 3 out of 4 fetuses in nearby clones. All these regions were tested in known databases and no copy number variations have been described for them. CONCLUSION: This is the first report of molecular characterization through a whole genome microarray CGH of fetuses with HPE. Our results may contribute to verify the effectiveness and applicability of the molecular technique of array CGH for prenatal diagnosis purposes, and contributing to the knowledge of the submicroscopic genomic instability characterization of HPE fetuses.